Drying of a tape-cast layer: Numerical investigation of influencing parameters. (May 2017) - Jabbari, M.; Shojaee Nasirabadi, P.; Jambhekar, V.A.; Hattel, J.H.; Helmig, R.
Highlights: Coupled free-flow-porous-media simulation on REV scale. Influence of process parameters on drying behaviour. Analysis of variance (ANOVA) for influencing parameters. Numerical results motivated by ceramic tape casting. Abstract: In this study, the evaporation of water from a ceramic-water mixture is investigated numerically with the purpose of understanding the drying process of the thin sheets produced by the tape casting process. In the scope of this work, a Representative Elementary Volume (REV) scale model concept for coupling non-isothermal multi-phase compositional porous-media flow and single-phase compositional laminar free-flow developed by Jabbari et al. (2016), is used for a thorough analysis of the influential parameters. Specifically, we investigate the influence of ventilation speed magnitude, v max, the equivalent diameter of particles of the porous medium, d p, the porosity of the porous medium, ϕ, the initial temperature in the free-flow region, T ff, and the initial temperature in the porous-medium region, T pm, on the characteristic drying curves of a thin ceramic layer. We, moreover, conduct a statistical analysis based on numerical experiments in combination with a fractional factorial design of the aforementioned parameters. The analysis accounts for the effects of parameters on the characteristic drying curves of a thin ceramic layer. The effects of varying each of the parameters as well as their mutual interaction are shown with particular attention to the maximal drying rate as well as the final time for the drying process.